EVALUASI RUANG KELAS ANAK USIA DINI SESUAI ASPEK PSIKOLOGI ARSITEKTUR - Refranisa; Sapcahadi, M.Arya; Febri, Salsabila (Jurnal Teknik Sipil dan Arsitektur, 2025)
TK Islam Al-Fath is a kindergarten level educational institution located in Pamulang District, South Tangerang City, Banten Province. The learning space facilities designed at the institution are flexible with an interior that uses bright colors designed to stimulate children's imagination and creativity. This is related to the application of architectural psychology which plays an important role in providing an environment that supports optimal child growth and development at an early age. This study aims to evaluate how much psychological aspects are applied to the classroom of TK Islam Al-Fath in order to determine factors such as the condition of furniture that is directly related to users, the condition of the spatial arrangement for users, the method used is observation of elements of architectural psychology. The results of this study indicate that in the design of the classroom, there needs to be adjustments in the selection of colors, flexibility of furniture, and lighting in order to create a more comfortable and conducive learning environment for children.